Behavioral Economics of Accounting: A Review of Archival Research on Individual Decision Makers*. (28th December 2021) - Hanlon, Michelle; Yeung, Kelvin; Zuo, Luo
ABSTRACT: This paper develops a unified framework to synthesize the growing stream of positive research on the role of individual decision makers in shaping observed accounting phenomena. This line of research recognizes two central ideas in behavioral economics. First, individual behavior depends not only on economic incentives and accessible information but also on individual preferences, abilities, experiences, and other characteristics. Second, the constraints that structure human interactions encompass both formal institutions (e.g., rules, laws, constitutions) and informal institutions (e.g., norms, conventions, rituals). Our review covers a broad set of individuals who are of interest in accounting research: managers, directors, audit partners, analysts, standard setters, politicians, judges, journalists, loan officers, financial advisors, and investors. We aim to understand the systematic effects of individual characteristics on a wide spectrum of accounting phenomena, including financial reporting, disclosure, tax planning, auditing, and corporate social responsibility. We highlight the importance of personal characteristics not only for an individual's own behavior but also for others' perceptions. Our review mainly focuses on archival research in accounting and provides some thoughts about opportunities for archival empiricists going forward. We also, when feasible, highlight opportunities for future field, survey, and experimental research. A central takeaway from our review is that individual‐level factors significantly improve our ability to explain and predict accounting phenomena beyond firm‐, industry‐, and market‐level factors. RÉSUMÉ: Économie comportementale de la comptabilité : examen de la recherche archivistique sur les décideurs individuels La présente étude élabore un cadre unifié pour effectuer une synthèse des recherches positives de plus en plus nombreuses sur le rôle que jouent les décideurs individuels pour façonner certains phénomènes comptables observés. Ce champ de recherche s'appuie sur deux idées centrales du domaine de l'économie comportementale. D'abord, le comportement individuel est tributaire non seulement des incitatifs économiques et de l'information accessible, mais également des préférences, des capacités, de l'expérience et d'autres caractéristiques individuelles. Ensuite, les contraintes qui structurent les interactions humaines englobent les institutions formelles (p. ex., règles, lois et constitutions) et les institutions informelles (p. ex., normes, conventions, rituels). Notre examen s'attarde à un vaste éventail de personnes qui présentent un intérêt pour la recherche comptable, soit les gestionnaires, directeurs, partenaires d'audit, analystes, normalisateurs, politiciens, juges, journalistes, responsables des prêts, conseillers financiers et investisseurs. Nous tentons de comprendre les effets systématiques des caractéristiques individuelles sur un vaste éventail de phénomènes comptables, notamment la communication et la divulgation d'information financière, la planification fiscale, l'audit et la responsabilité sociale des entreprises. Nous faisons ressortir l'importance des caractéristiques individuelles non seulement en lien avec le comportement des particuliers, mais aussi avec la perception des autres. Notre examen, qui s'appuie principalement sur la recherche archivistique en comptabilité, offre quelques réflexions sur les occasions qui s'offrent aux empiristes qui s'intéressent aux documents d'archives. En outre, lorsque c'était possible, nous avons proposé des possibilités d'études sur le terrain, d'enquêtes et de recherche expérimentale. Une des principales idées qui se dégage de notre examen est que certains facteurs individuels améliorent considérablement notre capacité à expliquer et à prédire les phénomènes comptables, au‐delà des facteurs à l'échelle de l'entreprise, du secteur d'activité et du marché.